'Human Rights' across time and space: a cross‐linguistic analysis of performatives in English and Italian. (26th March 2013) - Felici, Annarita
<x xml:space="preserve">Abstract</x> International treaties are usually drafted in one negotiated lingua franca and then translated into the other authentic languages. The quality of these translations must be uncontroversial because once authenticated, they become original versions with equivalent legal effect. This paper investigates semantic‐pragmatic aspects of performatives in the UN Declaration of Human Rights (UN 1948) and in the more recent EU Charter of Fundamental Rights (EU 2000), in English and Italian. Considering the 50 years elapsing between the publications of the two treaties, the analysis aims at ascertain translational equivalence and equivalent legal effects when rendering similar and in some cases, almost repetitive provisions. The comparison will ideally contribute to reflect on the implications of multilingual translation in the current global environment with special regard to legal instruments.